2018
DOI: 10.1111/ele.12952
|View full text |Cite
|
Sign up to set email alerts
|

Parasitic wasp‐associated symbiont affects plant‐mediated species interactions between herbivores

Abstract: Microbial mutualistic symbiosis is increasingly recognised as a hidden driving force in the ecology of plant-insect interactions. Although plant-associated and herbivore-associated symbionts clearly affect interactions between plants and herbivores, the effects of symbionts associated with higher trophic levels has been largely overlooked. At the third-trophic level, parasitic wasps are a common group of insects that can inject symbiotic viruses (polydnaviruses) and venom into their herbivorous hosts to suppor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
66
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 43 publications
(68 citation statements)
references
References 68 publications
1
66
0
1
Order By: Relevance
“…This may result from parasitoid infection modifying host's immune (Tan et al ., ) or metabolic (Potter and Woods, ; Mrinalini et al ., ) homeostasis that can further influence the intestinal microbial community. Several studies have recently reported an impact of polydnaviruses injected in the caterpillars through the venoms of parasitoid wasps (Cusumano et al ., ; Tan et al ., ; Zhu et al ., ). These symbiotic viruses induce changes in the caterpillar–plant interactions as well as in host immunity.…”
Section: Discussionmentioning
confidence: 98%
“…This may result from parasitoid infection modifying host's immune (Tan et al ., ) or metabolic (Potter and Woods, ; Mrinalini et al ., ) homeostasis that can further influence the intestinal microbial community. Several studies have recently reported an impact of polydnaviruses injected in the caterpillars through the venoms of parasitoid wasps (Cusumano et al ., ; Tan et al ., ; Zhu et al ., ). These symbiotic viruses induce changes in the caterpillar–plant interactions as well as in host immunity.…”
Section: Discussionmentioning
confidence: 98%
“…Thus, L. nana females appear to be partially capable of discriminating between hosts and non-hosts based on plant volatile blends released in response to feeding by parasitized caterpillars. The amount of feeding damage inflicted on plants (and thus the quantity of HIPVs released) depends on the parasitism status as well as by parasitoid identity of the attacking caterpillars (Poelman et al 2011; Cusumano et al 2018). Yet, bioassays using mechanically treated plants to standardize the amount of damage across treatments have shown the key role played by caterpillar oral secretions on foraging behavior of L. nana (Poelman et al 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Remarkably, the parasitoid species used in this study do not only inject eggs into their caterpillar hosts but also species-specific polydnaviruses (CgBV, CrBV, or HeIV) which, in addition to regulating host growth, also suppress the immune responses of the herbivores allowing parasitoid offspring to develop (Strand and Burke 2013; Doremus et al 2014; Drezen et al 2014). Recent findings have shown that polydnaviruses and not the parasitoid larvae developing within the herbivore body are the major drivers of specific changes induced by parasitism in plant responses including HIPV emission (Cusumano et al 2018; Tan et al 2018; Zhu et al 2018). Future studies should test the hypothesis that the polydnaviruses associated with the parasitoid species studied here are indeed major hidden players that allow L. nana to exploit HIPVs in a multi-parasitoid multi-herbivore scenario.…”
Section: Discussionmentioning
confidence: 99%
“…The microbiome is a broad term that defines the microscopic, symbiotic organisms associated with a particular host, and which can provide essential services for their host (e.g., aiding in immunity and digestion), thus providing insight into the health of the host organism (Fierer et al, ). The microbiome can have strong influence on the ecological niche occupied by the host species (Henry, Maiden, Ferrari, & Godfray, ; Hoffmann, Ross, & Rašić, ), and these symbiont‐induced changes to host ecology have increasingly clear impacts on the identity, strength, and outcome of interactions between hosts within communities (Berry & Widder, ; Cusumano et al, ; Frago, Dicke, & Godfray, ; Frago et al, ; Hrček, McLean, & Godfray, ; McLean, Parker, Hrček, Henry, & Godfray, ; Oliver, Smith, & Russell, ; Xie, Vilchez, & Mateos, ; Zhu et al, ). Understanding the spatiotemporal distribution and function of symbiont communities therefore has implications for basic and applied ecological theory.…”
Section: Introductionmentioning
confidence: 99%